Programa juegos de mesa para mejorar nociones de número y cantidad en niños de 4 años – I.E. Despertar, 2018 - Herrera Caballero, Merlin Rosmery (2020)
Nowadays, the little dissemination of strategies and the absence of ludic resources have generated a poor understanding of numbers and quantity in children. This research aims to improve the notions of number and quantity in four-year-old students of Despertar School, through the application of a Board Game Program. To get results of this quasi-experimental research, two groups were formed. In the first, the control group, a pre-test and a post-test were taken; while in the second, the experimental group, learning sessions were carried out. For the analysis of results, the application-descriptive method with statistical graphics was used, which allowed us to know about the notions of number and quantity by using the Board Game Program. It was concluded that the application of the Board Game Program significantly improves the notions of number and quantity in four-year-old children of Despertar School.